Joint Video Summarization and Transmission Adaptation for Energy-Efficient Wireless Video Streaming. (9th April 2008) - Li Li, Zhu Zhu; Zhai Zhai, Fan Fan; Katsaggelos Katsaggelos, Aggelos K. Aggelos K.
Abstract : The deployment of the higher data rate wireless infrastructure systems and the emerging convergence of voice, video, and data services have been driving various modern multimedia applications, such as video streaming and mobile TV. However, the greatest challenge for video transmission over an uplink multiaccess wireless channel is the limited channel bandwidth and battery energy of a mobile device. In this paper, we pursue an energy-efficient video communication solution through joint video summarization and transmission adaptation over a slow fading wireless channel. Video summarization, coding and modulation schemes, and packet transmission are optimally adapted to the unique packet arrival and delay characteristics of the video summaries. In addition to the optimal solution, we also propose a heuristic solution that has close-to-optimal performance. Operational energy efficiency versus video distortion performance is characterized under a summarization setting. Simulation results demonstrate the advantage of the proposed scheme in energy efficiency and video transmission quality.